329 Efficacy and safety of dupilumab treatment with concomitant topical corticosteroids in children aged 6 months to 5 years with severe atopic dermatitis. (25th January 2023) - Paller, Amy S; Pinter, Andreas; Lee, Lara Wine; Aschoff, Roland; Zdybski, Jacek; Schnopp, Christina; Praestgaard, Amy; Bansal, Ashish; Shumel, Brad; Prescilla, Randy; Bastian, Mike
Abstract: There are limited approved systemic treatment options for children with atopic dermatitis (AD). Dupilumab is now approved in the United States for patients 6 months and older with moderate-to-severe atopic dermatitis whose disease is not adequately controlled with topical prescription therapies. European Medicines Agency is evaluating the use of dupilumab in children aged 6 months through 5 years with severe AD only. To report the efficacy and safety of dupilumab in the subgroup of children aged 6 months to 5 years with severe AD (IGA score = 4) at baseline in the LIBERTY AD PRESCHOOL trial (NCT03346434 part B). Patients aged 6 months to 5 years with inadequately controlled moderate-to-severe AD were enrolled in LIBERTY AD PRESCHOOL (part B), a randomized, double-blind placebo-controlled phase 3 study. Patients were randomized to either dupilumab 200/300 mg every 4 weeks (200 mg if baseline weight 5 to <15 kg, 300 mg if 15 to <30 kg) or placebo for 16 weeks. All patients initiated standardized treatment with low-potency topical corticosteroids (TCS) from day –14. This analysis reports efficacy and quality-of-life endpoints including a 75% reduction from baseline in the Eczema Area and Severity Index (EASI-75), Peak-Pruritus Numerical Rating Scale (PP-NRS), Children's Dermatology Life Quality Index (CDLQI, for children aged 4 to <6 years), and Infant's Dermatitis Quality Of Life (IDQOL, for children <4 years) in children with severe AD. Of the total trial population of 162 patients with moderate-to-severe AD, 125 patients with severe AD at baseline were randomized: 63 to the dupilumab + TCS treatment group and 62 to the placebo + TCS treatment group. Baseline demographics were similar. Mean (SD) baseline disease characteristics were also similar between the dupilumab and placebo groups: EASI (38.8 [13.7] vs. 35.4 [12]), body surface area (63.1% [21] vs. 58.9% [21.4]), weekly average PP-NRS (7.6 [1.4] vs. 7.6 [1.6]), CDLQI (17.5 [5.5] vs. 17.8 [6.4]) and IDQOL (18.4 [5.1] vs. 17.4 [5.4]). Dupilumab treatment resulted in a rapid and significant increase in the proportion of patients achieving EASI-75 compared with placebo treatment by week 4 (27% vs. 4.8%; P = 0.0009). By week 16, this improvement was further increased compared with the placebo group (46% vs. 7%; P < 0.0001). At week 16, dupilumab-treated patients had a significantly greater percent reduction from baseline in PP-NRS compared with the placebo group (LS mean (SE)–41.8 [5.4] vs. 0.5 [5.4]; P < 0.0001). Dupilumab also resulted in significant improvement in quality-of-life outcomes compared with placebo (LS mean [SE]) change from baseline to week 16 in CDLQI (−9.1 [1.1] vs. −2.6 [1.2]; P < 0.0001); IDQOL (−9.1 [1.3] vs. −0.6 [1.1]; P < 0.0001). Treatment-emergent adverse events (TEAEs) were reported in 42 (66.7%) patients in the dupilumab group and 45 (73.8%) patients in the placebo group. Most TEAEs were mild to moderate and deemed unrelated to the study drug by the investigator. The most common TEAE was atopic dermatitis in both the dupilumab group (10 [15.9%]) and placebo group (16 [26.2%]). Additionally, TEAEs in the conjunctivitis cluster were reported by 4 (6.4%) patients in the dupilumab group and none in the placebo group. In the placebo group, 3 (4.9%) serious adverse events were reported. No dupilumab-related adverse events were serious or led to treatment discontinuation. Dupilumab significantly improved AD signs, symptoms, and quality of life in children aged 6 months to 5 years with severe AD. The safety profile was consistent with that previously seen in adults, adolescents, and children aged > 6 years of age.